ONE HUNDRED AND SEVENTY FIVE NEW SPECIES OF GRAPHIDACEAE—a special issue of Phytotaxa - Sohrabi, Mohammad; Lücking, Robert; Lumbsch, H. Thorsten (Phytotaxa, 2014)
The current issue of Phytotaxa is dedicated to a lichen-forming fungal family that forms an important component of tropical ecosystems. It is one of the most diverse families of lichenized fungi, with approximately 2,500 known species, and has its center of distribution in the wet tropics. The current issue sheds light on how poorly the species diversity of lichenized fungi is still known, with the description of 175 species new to science – all within a single family. We assembled 21 scientific papers, including three general publications and 18 papers focusing on description of new species.